Photodynamic Action of LED-Activated Curcumin against Staphylococcus aureus Involving Intracellular ROS Increase and Membrane Damage - Yuan Jiang; Albert Wingnang Leung; Heyu Hua; Xiancai Rao; Chuanshan Xu (International Journal of Photoenergy)
Aim. To investigate the effect of photodynamic action of LED-activated curcumin on cell viability, membrane permeability, and intracellular reactive oxygen species of Staphylococcus aureus. Methods. Staphylococcus aureus was incubated with the different concentrations of curcumin for 60 min and then irradiated by blue light with the wavelength of 470 nm and with light dose of 3 J/cm2. The colony forming unit assay was used to investigate photocytotoxicity of curcumin on Staphylococcus aureus, confocal laser scanning microscopy (CLSM) and flow cytometry (FCM) for assaying membrane permeability, FCM analysis with DCFH-DA staining for measuring the intracellular ROS level, and transmission electron microscopy (TEM) for observing morphology and structure. Results. Blue light-activated curcumin significantly killed Staphylococcus aureus in a curcumin dose-dependent manner. TEM observed remarkable structural damages in S. aureus after light-activated curcumin. More red fluorescence of PI dye was found in S. aureus treated by blue light-activated curcumin than in those of the controlled bacterial cells. Intracellular ROS increase was observed after light-activated curcumin. Conclusion. Blue light-activated curcumin markedly damaged membrane permeability, resulting in cell death of Staphylococcus aureus and highlighted that intracellular ROS increase might be an important event in photodynamic killing of Staphylococcus aureus in the presence of curcumin.